VIII. CONCLUSION: CO‐CONSTRUCTING A SECURE BASE PARTNERSHIP: MOTHER–CHILD INTERACTIONS, COMMUNICATION, AND SCRIPT REPRESENTATIONS. Issue 4 (5th December 2018) - Posada, Germán E.; Waters, Harriet S.
ABSTRACT: Using the secure base construct, the evidence presented indicates that interactional experience continues to be a central factor in the organization of mother–child attachment relationships. The parent–child codetermination process that establishes their relationship in infancy expands during the preschool years. Furthermore, with the increasingly relevant role of language, parent–child verbal communication during this time plays an important part in structuring children's attachment behavior and knowledge. Parents help their children construe attachment‐related information, control and regulate emotional experience, and guide behavior during attachment‐related experiences. That is, during early childhood, parent and child continue the process of constructing a secure base partnership through their gradually more complex interactions that take advantage of children's behavioral, emotional, representational, and language advances. Although the studies are interrelated and contribute to a coherent understanding of attachment relationships during this time period, they represent small‐scale studies. Further, some of the effect sizes presented are small. Thus, future research should include tests of replication as well as explorations of links to early and later development and parallel findings in more diverse samples.